A cross-sectional study of the experiences of distressed callers when accessing financial assistance from a telephone-based cancer information and support service - Elizabeth A. Fradgley; Paula Bridge; Katherine Lane; Danielle Spence; Della Yates; Melissa A. Carlson; Jo Taylor; Christine L. Paul (Australian and New Zealand Journal of Public Health)
Objective: The objective of this study was to explore the experiences of distressed people calling helplines regarding offer and uptake of financial services after cancer diagnosis. Methods: Cancer patients and caregivers reported whether they had discussed then used financial services and perceptions surrounding service uptake. Associations between being offered services and demographic, clinical and financial characteristics were explored. Results: Of the 508 patients and caregivers in this sample, 107 (21%) people who recalled discussing financial support used the service. Of those, 34 (32%) participants actioned a financial support referral, of which 32 (94%) reported that the support was helpful. Of the 401 (79%) who did not recall discussing financial support, 26 (6%) would have liked to do so. The following characteristics were significantly associated with a greater likelihood of discussing financial support: younger age, being married, metastatic disease, higher out-of-pocket costs, not having private health insurance, being on leave and being absent for more days from work. Conclusions: Although users of financial supports find them helpful, there is need for more structured approaches to referral to achieve equitable access. Implications for public health: A pro-active, structured approach to assessing financial toxicity and offering support is warranted in community-based organisations that offer cancer information and support.